PERAN JENDER DALAM RUMAH TANGGA PETANI RUMPUT LAUT DI KABUPATEN BUTON UTARA SULAWESI TENGGARA - Rosmawati Rosmawati; La Rianda; St. Aida Adha Taridala (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2015)
This study aims to determine the division of labor, gender households seaweed farmers in North Buton in productive activity, reproductive and social as well as access and control exerted by the husband and wife to some resources. The population is seaweed farming households totaling 246 households. The selected sample number is 71 households seaweed cultivators. Because this research in the gender perspective, then who will be interviewed are men and women in this case a husband and wife in every household seaweed farmers. Thus, the total number of respondents in this study as many as 142 people. The method used is descriptive analysis and Harvard Analytical Framework (HAF) methods. The results showed that the division of labor in productive and socially dominant husband than wife. In contrast to the division of reproductive, dominant wives than husbands. Husband and wife have equal access to the farm, while access to sources of capital, non-formal education, and information from the media, greater access the husband. In terms of decision-makers in the agricultural business, a more dominant role is husband. While in the sales process and the allocation of revenue there is a balance between the role of husband and wife. Key Words: access, control, gender role, seaweed.